Synthesis of Sine-on-Random vibration profiles for accelerated life tests based on fatigue damage spectrum equivalence. (15th March 2018) - Angeli, Andrea; Cornelis, Bram; Troncossi, Marco
Graphical abstract: Highlights: Accelerated life tests may be required for components subjected to vibrations. Standard PSD tests may be inadequate to represent real non-Gaussian environments. A Mission Synthesis procedure to obtain Sine-on-Random test profiles is proposed. The novel procedure is compared with the standard PSD methodology. Numerical and experimental results prove the superiority of Sine-on-Random tests. Abstract: In many real life environments, mechanical and electronic systems are subjected to vibrations that may induce dynamic loads and potentially lead to an early failure due to fatigue damage. Thus, qualification tests by means of shakers are advisable for the most critical components in order to verify their durability throughout the entire life cycle. Nowadays the trend is to tailor the qualification tests according to the specific application of the tested component, considering the measured field data as reference to set up the experimental campaign, for example through the so called "Mission Synthesis" methodology. One of the main issues is to define the excitation profiles for the tests, that must have, besides the (potentially scaled) frequency content, also the same damage potential of the field data despite being applied for a limited duration. With this target, the current procedures generally provide the test profile as a stationary random vibration specified by a Power Spectral Density (PSD). In certain applications this output may prove inadequate to represent the nature of the reference signal, and the procedure could result in an unrealistic qualification test. For instance when a rotating part is present in the system the component under analysis may be subjected to Sine-on-Random (SoR) vibrations, namely excitations composed of sinusoidal contributions superimposed to random vibrations. In this case, the synthesized test profile should preserve not only the induced fatigue damage but also the deterministic components of the environmental vibration. In this work, the potential advantages of a novel procedure to synthesize SoR profiles instead of PSDs for qualification tests are presented and supported by the results of an experimental campaign.